Screening for potential prophylactics targeting sporozoite motility through the skin - Douglas, Ross G.; Reinig, Miriam; Frischknecht, Friedrich (Malaria journal, 2018)
Anti-malarial compounds have not yet been identified that target the first obligatory step of infection in humans: the migration of Plasmodium sporozoites in the host dermis. This movement is essential to find and invade a blood vessel in order to be passively transported to the liver. Here, an imaging screening pipeline was established to screen for compounds capable of inhibiting extracellular sporozoites.
Gesehen am 25.09.2018